Mitochondrial-nuclear crosstalk, haplotype and copy number variation distinct in muscle fiber type, mitochondrial respiratory and metabolic enzyme activities. Issue 1 (December 2017) - Liu, Xuan; Trakooljul, Nares; Hadlich, Frieder; Murani, Eduard; Wimmers, Klaus; Ponsuksili, Siriluck
Abstract Genes expressed in mitochondria work in concert with those expressed in the nucleus to mediate oxidative phosphorylation (OXPHOS), a process that is relevant for muscle metabolism and meat quality. Mitochondrial genome activity can be efficiently studied and compared in Duroc and Pietrain pigs, which harbor different mitochondrial haplotypes and distinct muscle fiber types, mitochondrial respiratory activities, and fat content. Pietrain pigs homozygous-positive for malignant hyperthermia susceptibility (PiPP) carried only haplotype 8 and showed the lowest absolute mtDNA copy number accompanied by a decrease transcript abundance of mitochondrial-encoded subunitsND1, ND6, andATP6 and nuclear-encoded subunitsNDUFA11 and NDUFB8 . In contrast, we found that haplotype 4 of Duroc pigs had significantly higher mitochondrial DNA (mtDNA) copy numbers and an increase transcript abundance of mitochondrial-encoded subunitsND1, ND6, andATP6 . These results suggest that the variation in mitochondrial and nuclear genetic background among these animals has an effect on mitochondrial content and OXPHOS system subunit expression. We observed the co-expression pattern of mitochondrial and nuclear encoded OXPHOS subunits suggesting that the mitochondrial-nuclear crosstalk functionally involves in muscle metabolism. The findings provide valuable information for understanding muscle biology processes and energy metabolism, and may direct use for breeding strategies to improve meat quality and animal health.